1997
DOI: 10.1111/j.1600-0447.1997.tb10156.x
|View full text |Cite
|
Sign up to set email alerts
|

Folie à deux in Japan — analysis of 97 cases in the Japanese literature

Abstract: In order to clarify the characteristics of folie à deux in Japan, we examined a total of 97 cases of folie à deux in the Japanese literature covering a period of 90 years, and compared them with the cases reported in Western countries. About 75% of the Japanese cases occur in two individuals, and of these are family cases. The most common combinations are mother-child and married couple. Mother-child combinations are much more common than father-child combinations. Female subjects are more often involved than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
(2 reference statements)
0
27
0
1
Order By: Relevance
“…In folie a deux, delusions are usually persecutory [8] or grandiose, [9] although in our cases no delusion could be established either in primary or the secondary case. Usually, persons are closely associated for a long time and typically live together in relative social isolation.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 81%
“…In folie a deux, delusions are usually persecutory [8] or grandiose, [9] although in our cases no delusion could be established either in primary or the secondary case. Usually, persons are closely associated for a long time and typically live together in relative social isolation.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 81%
“…A review of 97 cases of shared psychotic disorder in Japan revealed the average age of dominant partner was 38 years old and average age of submissive partner was 36 years old. 4 Another review of 42 cases from 1993-2005 showed the mean age in primary patient was 52.7 and mean age in secondary patient was 45.9. 5 Nevertheless, shared psychotic disorder may present in any age group.…”
Section: Discussionmentioning
confidence: 99%
“…8 The disorder is more common in females than males for both primary and secondary patients. 4,5,9 Primary patients are typically observed to be more intelligent, older, and more aggressive/dominant whereas the secondary patients are generally younger, less intelligent, passive, and dependent. 3,10 Associated comorbidity in the primary patient Case Report of Shared Psychotic Disorder or 'Folie a Deux' in Two Geriatric Sisters …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations